10. DETERMINING FACTORS IN THE RETENTION OF HEALTH WORKERS WORKING IN HEALTH FACILITIES IN POOR DISTRICT (Vietnam Journal of Community Medicine, 2023)
Background: The lack of health workers in disadvantaged areas, especially in poor districts, hasexisted for many years.Objective: To analyze the factors affecting the retention and intention to continue working long-termof health workers in poor districts in 4 provinces of Dak Nong, Dien Bien, Ha Giang, and Nghe An,2022.Methods: Cross-sectional survey, quantitative study.Results: The study collected information from 492 health workers through questionnaires. Researchresults show that the background of health workers and commitment to work locally after receivingsupport for training are important factors in retaining health workers.Conclusion: The 2 most important factors in retaining health workers working in poor districts are:the health worker’s background is local (53%), receiving support for training and commitment towork in the locality after receiving support (37%). Factors related to the intention to work long-termin the poor district: level and field of work, training opportunities, commitment to work, and level ofjob satisfaction (p
Keywords: Retaining; health workers; poor district.